Metabolic Syndrome and Risk of Cervical Human Papillomavirus Incident and Persistent Infection - Huang, Xin; Zhao, Qun; Yang, Pingting; Li, Ying; Yuan, Hong; Wu, Liuxin; Chen, Zhiheng (Medicine (Baltimore), 2016)
Few studies have been conducted on the relationship between metabolic syndrome (MetS) and cervical human papillomavirus (HPV) incidence and persistent infection. We performed a prospective cohort study including 8598 female employees in Hunan, China. First, the subjects were stratified into HPV-negative (N = 7282) and HPV-positive (N = 1316) subgroups, according to the results of an HPV DNA test at baseline. Second, comparisons of the risks of HPV incident and persistent infection between MetS-positive (exposed) and MetS-negative (unexposed) groups were conducted among the HPV-negative and -positive subgroups, respectively. There were 976 (11.39%) subjects diagnosed with MetS and 1316 subjects diagnosed with HPV infection at baseline. The 12-month cumulative incidence of any type of HPV and high-risk type HPV were 7.28% (530/7282) and 6.26% (456/7282), respectively. Obesity was a modifier of the association between MetS and HPV incident infection. As long as obesity presented, MetS and hypertriglyceridemia were significantly associated with an increased risk of HPV incident infection (any-type or high-risk type) (adjusted risk ratios (RR) were 2.88 (95% confidence interval (CI): 1.16, 7.19) and 3.29 (95% CI: 1.47, 7.38), respectively). Among those infected with HPV at baseline, the 12-month type-specific persistence rates were 51.67% and 53.38% for any-type and high-risk type HPV, respectively. No interaction was found between obesity and MetS with regard to the risk of HPV persistence. After adjustment for confounding factors, MetS was still associated with increased risk of any-type HPV persistence (RRadj = 1.21, 95% CI: 1.05, 1.41) and high-risk type HPV persistence (RRadj = 1.25, 95% CI: 1.09, 1.46). No single metabolic component was associated with the risk of HPV persistence. The prevalence of MetS was 11.39% among the Hunan female occupational population. MetS was associated with an increased risk of persistent cervical HPV infection and also with an increased risk of HPV incident infection when obesity presented as well.